2003
DOI: 10.1038/sj.onc.1206333
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional interaction between HCV core protein and the different p73 isoforms

Abstract: Hepatitis C virus (HCV) core protein is a structural viral protein that packages the viral genomic RNA. In addition to this function, HCV core also modulates a number of cellular regulatory functions. In fact, HCV core protein has been found to modulate the expression of the cyclindependent inhibitor p21 WAF1/CIP1 and to promote both apoptosis and cell proliferation through its physical interaction with p53. Here, we studied the ability of HCV core to bind the p53-related p73 protein, its isoforms and its dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 43 publications
1
47
0
1
Order By: Relevance
“…Moreover, it has also been shown to induce hepatic adenomas in transgenic mice. These adenomas typically progress morphologically and biochemically to full malignant HCC (29). In this report, we evaluated the relationships between stable HCV core protein expression and its impact on the different cyclin-CDK complex activities involved in the control of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has also been shown to induce hepatic adenomas in transgenic mice. These adenomas typically progress morphologically and biochemically to full malignant HCC (29). In this report, we evaluated the relationships between stable HCV core protein expression and its impact on the different cyclin-CDK complex activities involved in the control of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…p73/core interaction results in the nuclear translocation of HCV core protein in the presence of the either p73a or p73b tumour suppressor proteins. The interaction with HCV core protein prevents p73a-, but not p73b-dependent cell growth arrest in a p53-dependent manner (Alisi et al, 2003). Hepatitis C virus core protein also modulates the expression of the cyclin-dependent kinase (CDK) inhibitor p21/Waf .…”
Section: Hepatitis C Virus Proteins and Host-cell Factorsmentioning
confidence: 99%
“…Hepatitis C virus core binds to the p53 (Ray et al, 1997;Lu et al, 1999), p73 (Alisi et al, 2003) and pRb (Cho et al, 2001) tumor suppressor proteins, but the functional consequences of these interactions have not fully been elucidated. p73/core interaction results in the nuclear translocation of HCV core protein in the presence of the either p73a or p73b tumour suppressor proteins.…”
Section: Hepatitis C Virus Proteins and Host-cell Factorsmentioning
confidence: 99%
“…5). It has been shown that the p73 protein is regulated by diverse factors, including MDM2, MDMX, p300/ CBP, Amphiphysin IIb-1, ASPP (apoptosis-stimulated proteins of p53) 1 and 2, c-Abl (cellular Abelson oncogene), c-Myc, CTF2 (CCAATbinding transcription factor 2), Cyclin G, HCV (hepatitis C virus protein), MM1, PMS2 (mismatch-repair protein s2), WT1 (Wilms tumor protein), and YAP (Yes-associated protein) (15,16,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Among these regulators, MDM2 is a well known repressor of p73 and p53, but its inhibitory effect on p73 does not involve degradation.…”
Section: P19mentioning
confidence: 99%